Penerapan Sistem Informasi Akuntansi Pada Peternakan Ayam Petelur “X” - Andri Gunawan; Alexander Setiawan; Djoni Haryadi Setiabudi (Jurnal Infra, 2020)
At this time, the ‘X’ laying chicken farm in the Pare city has not yet implemented an accounting information system. All operational transaction records are still carried out manually so that it is prone to losing important data, making it difficult for farm owners to know his business developments. Because of the problem, then an accounting information system was designed with the assumption of an average inventory. This application uses the programming language PHP and MySql.    Based on the results obtained from this application include recording card stock, recording transactions both purchases and sales, recording maintenance, recording debt and receivables, and basic accounting reports in the form of income statements, balance sheets, journals, and ledgers.